PRACTICE AND FUTURE OF ENERGY-EFFICIENT CONSTRUCTION IN THE REPUBLIC OF KAZAKHSTAN - Sharipov, Rashid; Tyulyubayeva, Dinara; Shavdinova, Madina; Kudrevich, Olga; Yerzhanov, Syrymgali (Journal of Applied Engineering Science, 2020)
The article touches upon the problem of energy saving and increasing energy efficiency in the construction sector, which consumes a significant share of the country's energy resources. The issues of rational use of energy resources with the aspects of energy saving, energy efficiency and, correspondingly, environmental problems are becoming increasingly important, and their solution has become a strategic task for Kazakhstan. In order to give momentum to energy saving measures carried out in Kazakhstan, a number of laws, bylaws and programs related to the rational use of energy resources and energy efficiency have been adopted. To solve this problem, it is planned to carry out targeted measures to eliminate existing political, legislative, technical and information barriers. A regulatory technical base is being developed based on the most recent advances of construction science.
Keywords: energy saving and energy efficiency improvement; regulatory technical documents; secondary and renewable energy resources; heat consumption in buildings; design and construction of energy-efficient buildings; “green” economy; efficient ventilation systems